2014
DOI: 10.3389/fchem.2014.00050
|View full text |Cite
|
Sign up to set email alerts
|

Human isoprenoid synthase enzymes as therapeutic targets

Abstract: In the human body, the complex biochemical network known as the mevalonate pathway is responsible for the biosynthesis of all isoprenoids, which consists of a vast array of metabolites that are vital for proper cellular functions. Two key isoprenoids, farnesyl pyrophosphate (FPP) and geranylgeranyl pyrophosphate (GGPP) are responsible for the post-translational prenylation of small GTP-binding proteins, and serve as the biosynthetic precursors to numerous other biomolecules. The down-stream metabolite of FPP a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 174 publications
(214 reference statements)
1
45
0
1
Order By: Relevance
“…Because of the inclusion criteria, total cholesterol and LDL‐C levels were elevated in all participants of our study. However, although vitamin D and cholesterol share a common precursor (7‐dehydrocholesterol), patients with normal and low 25‐hydroxyvitamin D levels did not differ in baseline circulating levels of plasma lipids. This finding, which is in line with a neutral effect of vitamin D preparations on plasma lipids levels, as well as the lack of correlations between levels of 25‐hydroxyvitamin D and plasma lipids, suggest that vitamin D status plays a relatively small role in the regulation of lipid production and metabolism.…”
Section: Discussionmentioning
confidence: 83%
“…Because of the inclusion criteria, total cholesterol and LDL‐C levels were elevated in all participants of our study. However, although vitamin D and cholesterol share a common precursor (7‐dehydrocholesterol), patients with normal and low 25‐hydroxyvitamin D levels did not differ in baseline circulating levels of plasma lipids. This finding, which is in line with a neutral effect of vitamin D preparations on plasma lipids levels, as well as the lack of correlations between levels of 25‐hydroxyvitamin D and plasma lipids, suggest that vitamin D status plays a relatively small role in the regulation of lipid production and metabolism.…”
Section: Discussionmentioning
confidence: 83%
“…Hepatocytes are the major target for statin drugs where they inhibit HMG-CoA reductase enzyme. Statins, not only compete with the substrate in enzyme active site, but also they induce a conformational change in the enzyme's structure [56]. In addition, a series of processes leading to increased synthesis of NO by endothelial cells, reduction of cholesterol accumulation in macrophages, regression of atherosclerotic plaque, inflammatory process, inhibition of the platelet aggregation, alteration in intracellular calcium homeostasis and inhibition of tumor cells growth are all modulated by statins [57].…”
Section: Pleiotropic Effects Of Statins and Their Action On Reducing mentioning
confidence: 99%
“…The inhibition of FPPS suppresses geranylation and farnesylation of several key proteins, which in turn activates the production of cell signaling molecules to stop osteoclastic activities [1-9]. Interestingly, in vitro studies also demonstrated that FPPS inhibition can decrease cell proliferation and migration, as well as induce apoptosis [1, 10]. In addition, a number of in vitro and clinical studies demonstrated that Zol efficiently inhibits basic fibroblast growth factor (bFGF) and vascular endothelial growth factor (VEGF) signaling, thus inhibiting blood vessel growth in a tumor [11, 12].…”
Section: Introductionmentioning
confidence: 99%